The chemoprotection of a blueberry anthocyanin extract against the acrylamide-induced oxidative stress in mitochondria: unequivocal evidence in mice liver. Issue 9 (2nd September 2015) - Zhao, Mengyao; Wang, Pengpu; Zhu, Yuchen; Liu, Xin; Hu, Xiaosong; Chen, Fang
<x xml:space="preserve">Abstract</x> The mitochondrial mechanism of Acrylamide-induced oxidative stress.